Effect of Growth Regulator on Regeneration of Two Sweet Potatoes (Ipomoea batatas L.) (Journal of Environmental Science and Natural Resources, 2015)
The experiment was conducted to investigate the effect of various concentrations of different growth regulators on the aspect of callus induction along with shoot regeneration and root formation of two sweet potato varieties viz. BARI 6 and BARI 7. For callus induction, MS medium was used supplemented with different concentrations of 2,4D (0, 0.1, 0.5 and 1.0 mg L1) and Kinetin (0, 0.1, 0.5 and 1.0 mg L1)). Different concentrations of BAP (0, 1.5, 2.5, 3.5 and 4.5 mg L1) were used for shoot regeneration while different concentrations of NAA (0, 0.1, 0.5, 1.0 and 1.5) with a constant level of BAP @ 2.0 were also used for root development. All the studied parameters were significantly influenced by the effect of sweet potato varieties and various concentrations of growth regulators. The highest percentage (91.67%) of callus induction was observed in 0.5 mg L1 2,4D + 0.5 mg L1 kinetin with the variety BARI 6 within a minimum number of days (5.50 days) while similar effect also showed the higher weight of callus at 15 (4.65 g) and 35 (6.12 g) days of culture. Performance study of BAP concentration regarding two potato varieties were significant among the shoot characters where 2.5 mg L1 BAP treated callus of BARI6 obtained the maximum regeneration of shoot (85.00%) with an average requiring minimum time (6.83 days) while maximum leaves shoot1 (12.17) and longest shoot (5.50 cm) were also obtained. Percentage of root formation (73.33%) had also maximum in BARI6 with an average requiring least time (6.83 days) while it was treated by 1.0 mg L1 NAA which treatment also showed the longest root (10.83 cm).So, it is clear that the sweet potato variety BARI6 showed superiority than BARI7 while 0.5 mg L1 2,4D + 0.5 mg L1 kinetin was the best combination for callus induction, 2.5 mg L1 BAP for shoot formation and 1.0 mg L1 NAA for root regeneration in the present study.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22156 J. Environ. Sci. & Natural Resources, 7(1): 113-116 2014